Myocardial Recovery in Patients Receiving Contemporary Left Ventricular Assist Devices: Results From the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS). (July 2016) - Topkara, Veli K.; Garan, A. Reshad; Fine, Barry; Godier-Furnémont, Amandine F.; Breskin, Alexander; Cagliostro, Barbara; Yuzefpolskaya, Melana; Takeda, Koji; Takayama, Hiroo; Mancini, Donna M.; Naka, Yoshifumi; Colombo, Paolo C.
Abstract : Background—: Time course and predictors of myocardial recovery on contemporary left ventricular assist device support are poorly defined because of limited number of recovery patients at any implanting center. This study sought to investigate myocardial recovery using multicenter data from the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS). Methods and Results—: Thirteen thousand four hundred fifty-four adult patients were studied. Device explant rates for myocardial recovery were 0.9% at 1-year, 1.9% at 2-year, and 3.1% at 3-year follow-up. Independent predictors of device explantation for recovery were age <50 years (odds ratio [OR] 2.5), nonischemic etiology (OR 5.4), time since initial diagnosis <2 years (OR 3.4), suboptimal heart failure therapy before implant (OR 2.2), left ventricular end-diastolic diameter <6.5 cm (OR 1.7), pulmonary systolic artery pressure <50 mm Hg (OR 2.0), blood urea nitrogen <30 mg/dL (OR 3.3), and axial-flow device (OR 7.6). Patients with myocarditis (7.7%), postpartum cardiomyopathy (4.4%), and adriamycin-induced cardiomyopathy (4.1%) had highest rates of device explantation for recovery. Use of neurohormonal blockers on left ventricular assist device support was significantly higher in patients who were explanted for recovery. Importantly, 9% of all left ventricular assist device patients who were not explanted for recovery have demonstrated substantial improvement in left ventricular ejection fraction (partial recovery) and had remarkable overlap in clinical characteristic profile compared with patients who were explanted for recovery (complete recovery). Complete and partial recovery rates have declined in parallel with recent changes observed in device indications and technology. Conclusions—: Myocardial recovery is a spectrum of improvement rather than a binary clinical end point. One in every 10 left ventricular assist device patients demonstrates partial or complete myocardial recovery and should be targeted for functional assessment and optimization. Abstract : Supplemental Digital Content is available in the text.